Adolescents with Physical Disabilities and Their Wellbeing and Peer Relationships Within Secondary Schools in Iceland - Edda Þorvarðardóttir 1992- (2014)
Previous research has shown that adolescents with physical disabilities find it more challenging to integrate into the school system and do not always feel included in their peer group. They appeared to be more solitary than is the norm; especially during break times. They were also less likely to be chosen as playmates and had fewer friends than able-bodied adolescents. Furthermore, disabled adolescents said that they experienced social exclusion both from teachers and their peers that often lead to verbal and physical bullying. In this research, the wellbeing of students with physical disabilities in their school environment will be estimated. The data was from a larger dataset used in investigations of the Icelandic Centre for Social Research and Analysis (ICSRA). The sample, used in this study, consists of 2565 students, of which 628 reported having a physical disability. The results were analyzed to ascertain whether the presence of a physical disability had a significant effect on adolescents. The results showed a disparity between disabled and able-bodied adolescents where disabled adolescents had lower levels of wellbeing in school and their peer relationships were not as well developed. Rannsóknir hafa sýnt að ungmennum með líkamlega fötlun þykir erfiðara að aðlagast skólakerfinu og finnst þau oft ekki vera hluti af hópnum. Þau þykja vera meira ein en þykir eðlilegt, sérstaklega í frímínútum og eru sjaldnar valin sem leikfélagar og eiga því færri vini. Þá finnst þeim þau upplifa félagslega útilokun frá bæði kennurum og skólafélögum sem í mörgum tilfellum endar með munnlegu eða líkamlegu einelti. Í þessari rannsókn verður skoðuð líðan ungmenna með líkamlega fötlun í framhaldsskólum á Íslandi. Gögnin eru fengin úr stærra gagnasafni frá Rannsóknum og greiningu. Úrtakið sem notast er við í þessari rannsókn inniheldur 2565 nemendur. Þar af eru 628 einstaklingar sem svara því að þeir glími við líkamlega fötlun. Við yfirferð á niðurstöðum var skoðað hvort það skipti máli að vera með líkamlega fötlun eða ...